Voxel-size dependent quantitative susceptibility mapping of blood vessel networks: a simulation study - Buschle, Lukas R.; Kurz, Felix T.; Sturm, Volker Jörg Friedrich; Schlemmer, Heinz-Peter; Ziener, Christian H. (Zeitschrift für medizinische Physik, 2019)
Quantitative susceptibility mapping provides a measure for the local susceptibility within a voxel in magnetic resonance imaging (MRI). So far, theoretical and numerical studies focus on the assumption of a constant susceptibility inside each MR voxel. For blood vessel networks, however, susceptibility differences between blood and surrounding tissue occur on a much smaller length scale than the typical voxel size in routine MRI. In this work, the dependency of the quantitative susceptibility value on vessel size and voxel size is analyzed.